2022
DOI: 10.3390/diagnostics12102384
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Limitations of OCT-A in the Diagnosis and Follow-Up of Posterior Intraocular Inflammation in Current Clinical Practice: A Valuable Tool or a Deceiver?

Abstract: Purpose: Optical coherence tomography angiography (OCT-A) has been applied to uveitis and intraocular inflammation since its availability after 2014. The imaging of retinal and choroidal vascularization without the use of dyes was a major development and represented a potentially valuable tool in ocular research. In addition to such use, OCT-A is often put forward as being able to potentially replace invasive methods needing dye injection, such as fluorescein angiography (FA) and indocyanine green angiography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…However, a study by Herbort et al highlights the limitations of OCTA in the diagnosis and follow-up of posterior intraocular inflammation, and suggests that it should be used in combination with other imaging modalities and clinical examination. The study also suggests that the interpretation of OCTA images requires a high level of expertise, and that false positive and false negative results can occur if the images are not properly interpreted (24).…”
Section: Uveitismentioning
confidence: 94%
“…However, a study by Herbort et al highlights the limitations of OCTA in the diagnosis and follow-up of posterior intraocular inflammation, and suggests that it should be used in combination with other imaging modalities and clinical examination. The study also suggests that the interpretation of OCTA images requires a high level of expertise, and that false positive and false negative results can occur if the images are not properly interpreted (24).…”
Section: Uveitismentioning
confidence: 94%
“…Thanks to a semiquantitative angiographic scoring system the proportion of inflammatory involvement in both structures can be calculated. [7,26] The proportion of respective involvement can be very different from one case to another as shown in figures 24 Figure 23. Extreme sensitivity and global information on whole fundus involvement given by ICGA.…”
Section: Sarcoidosis Chorioretinitismentioning
confidence: 97%
“…The limited field of view in commercially available instruments is a major disadvantage, as is the case for OCT, when compared to dye exams. The presentation of the retinal vasculature and choriocapillaris without the use of a dye was a revolution which led to theories that OCT-A could replace the dye exams which is absolutely not the case [24,25], but nevertheless stimulated the publication of articles attempting to oppose the two methodologies [26,27]. Indeed, OCT-A is of limited practical value in everyday routine clinical practice with limited valueadded information after other multimodal investigations have been performed [28].…”
Section: Optical Coherence Tomography Angiography (Oct-a)mentioning
confidence: 99%
“…The study also showed that OCTA was able to detect inflammation in areas that were not visible on clinical examination, suggesting that it may be able to identify early stages of inflammation. 43 It should be noted that a study by Herbort et al 44 highlighted the limitations of OCTA in the diagnosis and follow-up of posterior intraocular inflammation, and the findings suggested that it should be used in combination with other imaging modalities and clinical examination. The study also suggested that the interpretation of OCTA images requires a high level of expertise and that false-positive and false-negative results can occur if the images are not properly interpreted.…”
Section: Uveitismentioning
confidence: 99%
“…The study also suggested that the interpretation of OCTA images requires a high level of expertise and that false-positive and false-negative results can occur if the images are not properly interpreted. 44 …”
Section: Clinical Uses Of Octa In Current Ophthalmic Practicementioning
confidence: 99%